Toxoplasma gondii Coinfection in HIV/AIDS Patients of Dr. Moewardi Hospital in Surakarta - Raharjo, Irvan; Sari, Yulia; Prasetyo, Afiono Agung (Nexus Biomedika, 2015)
Background: Coinfection of T. gondii and HIV/AIDS will result in severe clinical symptoms. Age and gender are risk factors that are often associated with the occurrence of this coinfection. This study aimed to determine the seroprevalence of T. gondii and HIV/AIDS coinfection as well as to determine its association with age and gender. Methods: Serological test, ELISA, was performed in order to determine the presence of IgM anti-Toxo and IgG anti-Toxo in 51 blood samples taken from HIV/AIDS patients at Dr. Moewardi Hospital in November 2011. Results: The positive rates of IgM anti-Toxo and IgG anti-Toxo were 25.5% (13/51) and 17.6% (9/51), respectively. IgM anti-Toxo was associated with age â¥ 37 years (aOR 9.34 (95% CI 1.775â49.174; p = 0.008)). Unless otherwise stated, no statistical association could be drawn. Conclusions: Screening on T. gondii infection is recommended for all HIV/AIDS patients since the positivity rates of anti-Toxo antibodies were found high in these patients. Keywords: Toxoplasma gondii, HIV/AIDS coinfectionÂ